A Single Phase Parallel Active Power Line Conditioner for Harmonic Elimination - M.Kala Rathi (International Journal of Advanced Science and Technology, 2020)
Lately there has been a widespread usage of power electronic devices in a lot of applications for the reason that they offer improved controllability and efficacy. These power electronic based loads exhibit non-linear characteristics and hence commonly known as nonlinear loads. Some frequently used single phase non-linear loads such as domestic lights, oven, computer power supply etc cause power quality problems by injecting harmonics. In this work, a parallel Active Power Line Conditioner (APLC) based on single phase inverter with capacitor on the DC side has been used for mitigation of harmonics in a single phase system. A mean power theory with phase detector extracts the reference currents and Hysteresis Current Controller (HCC) generates gating signal. A simple Proportional Integral (PI) controller retains the inverter DC voltage at a reference value which is vital for right harmonic compensation. The system is developed in MATLAB and its performance is validated by considering different non-linear loads such as single phase diode bridge rectifier with RL and RC load on the DC side. The results attained from simulation reveals the developed system mitigates harmonics efficiently.